ENDEMIC MICROSNAIL SHEITANOK AMIDICUS (CAENOGASTROPODA: HYDROBIIDAE) ADDITIONAL LOCATIONS, DISTRIBUTION, SHELL MORPHOLOGY, AND NEAR-THREATENED - Ekin, Ihsan (Conchological Soc Great Britain & Ireland, 2023)
The endemic microsnail Sheitanok amidicus (Schutt & Sesen, 1991) was investigated to update its distribution and to raise awareness of its near-threatened status. S. amidicus specimens from Tulluk village (Paratype) (Devegecidi Bridge, Diyarbakir), Kozluk town (Batman), Savur town (Mardin) and Elmabahce village (Mardin) were obtained from the Museum of Zoology, Dicle University, Diyarbakir, Turkiye. Kozluk, Savur and Elmabahce locations were not specified in the previous studies of collectors Schutt and Sesen. As a result of the surveys conducted at four springs in 2022, it was observed that the Tulluk spring was filled with construction debris, the Herbik spring (Elmabahce) had dried up, and the level of water in Kozluk and Savur springs had significantly decreased. Some samples were collected from the Savur and Kozluk springs for comparison and confirmation. The species has an average shell size of 1.2-1.4mm wide and 0.8-1.0mm high and contains 3.5 or 4 highly convex whorls with moderately deep sutures that widen towards the aperture. Since S. amidicus lives in shallow springs, it quickly disappears when the source dries up. Notably, the species is in the IUCN Red List of threatened species as a near-threatened category. As a result, this current research could lead to conservation measures to protect the species from extinction. Furthermore, by reporting the colourful images and morphological features of this rare snail, which is the sole species in the genus, recording of the genus will be easier and more accurate.
Keywords: Endemic; Near-threatened; Sheitanok amidicus; SE Turkiye